Change management of socially relevant habits - Gerold Behrens; Maria Neumaier (Management Revue, 2009)
It is sometimes necessary for the state to take intrusive measures into the life of its citizens in order to attain higher social goals. When circumstances require it, the force of law may be used (e.g. smoking prohibition, obligation to wear seat belts whilst driving), but on the whole it is more appropriate in a democracy to seek behavioral change by educational means (e.g. information about healthy nutrition). It has been shown that awareness of a problem can be brought about in this way, but that awareness alone does not lead to lasting behavioral change: between these two steps there is an inner barrier, and it is this that the present paper seeks to investigate. The perspective chosen is that of the neural sciences, as this covers motor and other unconscious processes. Within this framework a concept for social change management will be developed and illustrated with practical examples.
Keywords: 650; political change management; voluntary action; behavioral change; motor processes